The strategy of industry development as a factor of competitive advantages realization - Leyla M. Gusieva, Zarema N. Yagumova, Salih A. Bayzulayev, Elmira G. Shurdumova, Zalina H. Gergova (Opción, 2019)
The study aims to investigate conceptual foundations of strategy of Russian industry development as a factor of competitive advantages realization on the international market via documentary and qualitative comparative analysis of previous works. The article substantiates that the economic viability and the efficiency of socio-economic development of the national economy always depends, first of all, on its competitiveness. In conclusion, the Russian mechanical engineering industry in its current state, characterized by a high degree of fixed assets depreciation, low productivity and weak innovative component of production, requires a more detailed approach to improve the competitiveness of its enterprises.